Pengakuan Hak Konstitusional Pengelolaan Sumber Daya Industri Ekstraktif dalam Mewujudkan Kesejahteraan Rakyat - Husna TR, Cut Asmaul (Mahkamah Konstitusi Republik Indonesia, 2014)
Resource management, extractive industries have a significant role to state revenues. Extractive industries sector in Indonesia is a very closed industry sectors primarily on revenues derived from state income Cooperation Contract (KKS). Resource management paradigm for the extractive industries exploited only to pursue exchange of reliance State Budget (Budget) by denying the maximum prosperity for the people. Globalization can not be avoided has affected the existence of Law No. 22 of 2001 on Oil and Gas value-laden liberal-capitalistic. Consequently, there has been a paradigm shift in both the PSC and the people of the country to the tyranny of capital resulted in the country and people can not renegotiate the contract. Therefore, reform of the legal arrangements in the extractive industries absolutely must be done in order to realize the people’s welfare. Urgency juridical formation of the Draft Law on Amendments of Law No. 22 of 2001, based on the decision of the Constitutional Court Case No. 002/PUU-I/2003 and Decision No. 36/PUU-X/2012. Just and prosperous society, as a goal, requires the struggle to create the basics, which is referred to as the national interests of the Indonesian people. All efforts and actions to ensure the implementation of state remains fixed on the terminus ad quem, just and prosperous society.